PEMBEBASAN BERSYARAT NARAPIDANA TERORISME SEBAGAI UPAYA DERADIKALISASI DI LEMBAGA PEMASYARAKATAN KELAS IIB NGAWI - Teguh Widodo; S. Andi Sutrasno; Heru Dradjat Sulistyo (Bajang Institute, 2025)
Terrorism action exerts adverse impact on a state, in either defense or economic sector; therefore, it is always threatened with severe punishment by the criminal law in the state jurisdiction. The release of Law Number 5 of 2018 gives new color to the management of terrorism crime, in which the government holds deradicalization program for terrorism convict. This research aims to study the Republic of Indonesia Ministry of Law and Human Rights’ Decree Number PAS-1931.PK.05.09 of 2023 about Parole for Terrorism Convict in realizing the deradicalization attempt. The existence of deradicalization in the attempt of reducing radical activity and neutralizing radicalism for those involved in terrorism crime. This program is held as an attempt of paroling the terrorism crime. The weakness found in the implementation of deradicalization program is that there is no parameter concerning the successfulness level so that there is no parameter of achievement and the subject or the target of deradicalization is not obvious. Some contraints are found in the implementation of deradicalization: the convicts still hold on their ideology tightly, do not have fund, and their life is endangered by their group when they are free later. This research recommends the improvement of coordination between National Counter-Terrorism Agency (BNPT), Resort Police, Military District Command (Kodim), District Court, Religion Court, and Penitentiary to smooth the parole process and the increase in the number of Officers dealing with Terrorism Convicts